Governing the galleys : jurisdiction, justice, and trade in the squadrons of the hispanic monarchy (sixteenth-seventeenth centuries) - Lomas Cortés, Manuel (Mediterranean reconfigurations, 2020)
"The study of galleys is no longer confined to the history of events, navigation, or tactics. The classic paradigm has gradually been transformed: essentially descriptive- of types of ships and their components, or of the number and composition of their crews- it also served nationalist ends. The affirmation of an epic, glorious past could legitimate a nation's identity and its role in building the political, legal, and cultural reality of the modern- day Mediterranean"--